2021
DOI: 10.1002/cnr2.1382
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on cervical cancer, attitude toward its screening, and associated factors among reproductive age women in Metu Town, Ilu Aba Bor, South West Ethiopia, 2018: community‐based cross‐sectional study

Abstract: Background: Cervical cancer is one of the major public health problems worldwide.Lack of awareness and unavailability of screening services are the major factors that contribute to the problem of cervical cancer in Ethiopia. The community-based study conducted regarding the knowledge and attitude toward cervical cancer among women of reproductive age group is not enough to indicate the problem.Aim: To assess the knowledge on cervical cancer, attitude toward its screening, and associated factors among women of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The majority of the articles reported that about 50% and more of the study participants were not knowledge about cervical cancer, prevention, and services (19,22,77,78). Similarly, about half or more women had an unfavourable attitude except in a few studies that reported better attitude coverage (14,23,77,79,80). Knowledge was frequently reported as a precursor to a favourable attitude (16, 26, 81).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the articles reported that about 50% and more of the study participants were not knowledge about cervical cancer, prevention, and services (19,22,77,78). Similarly, about half or more women had an unfavourable attitude except in a few studies that reported better attitude coverage (14,23,77,79,80). Knowledge was frequently reported as a precursor to a favourable attitude (16, 26, 81).…”
Section: Discussionmentioning
confidence: 99%
“… 14 – 17 The study conducted in Northern and southwestern Ethiopia also identified that level of education, lack of awareness about CC screening, occupation, having children, and visiting health facilities were the determinant factors associated with the uptaking of cervical cancer screening. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] The study conducted in Northern and southwestern Ethiopia also identified that level of education, lack of awareness about CC screening, occupation, having children, and visiting health facilities were the determinant factors associated with the uptaking of cervical cancer screening. 18,19 Regular and early screening and treatment as part of targeted interventions is mandatory to reduce the incidence and mortality associated with the cervical cancer. But there are very limited studies conducted in the country, specifically in the study area to assess the utilization of cervical cancer screening service.…”
Section: Introductionmentioning
confidence: 99%